2009
DOI: 10.1080/14733140902914604
|View full text |Cite
|
Sign up to set email alerts
|

Who drops‐out? Do measures of risk to self and to others predict unplanned endings in primary care counselling?

Abstract: Aims: Unplanned endings, where clients unilaterally end therapy, are of concern for psychological therapy services generally as they raise questions about the appropriateness of the treatment and it's delivery for some clients. Limited available data indicates that those who drop‐out often have more severe symptoms at entry, and have poorer clinical outcomes. This raises further questions about risk to self and others for those clients who leave therapy prematurely and how these clients might be identified and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…For dropout, the patient variables identified were similar to those reported elsewhere: greater symptom severity at intake (Kazdin, Mazurick, & Siegel, 1994); younger age (e.g., Edlund et al, 2002), and non- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w white ethnicity and unemployment, which may be proxy measures of socio-economic deprivation (Garfield, 1994;Wierzbiki & Pekarik, 1993;Williams, Ketring, & Salts, 2005). In addition, and possibly of greater concern, was the finding that patients at risk of harming themselves or others were more likely to dropout than patients with no risk, a finding that supports previous research from a single service study using CORE risk items (Saxon, Ricketts & Heywood, 2010). We found that patients who had been 'physically violent to others' were 39% more likely to dropout than those who had not.…”
Section: Case-mix Variablessupporting
confidence: 86%
“…For dropout, the patient variables identified were similar to those reported elsewhere: greater symptom severity at intake (Kazdin, Mazurick, & Siegel, 1994); younger age (e.g., Edlund et al, 2002), and non- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w white ethnicity and unemployment, which may be proxy measures of socio-economic deprivation (Garfield, 1994;Wierzbiki & Pekarik, 1993;Williams, Ketring, & Salts, 2005). In addition, and possibly of greater concern, was the finding that patients at risk of harming themselves or others were more likely to dropout than patients with no risk, a finding that supports previous research from a single service study using CORE risk items (Saxon, Ricketts & Heywood, 2010). We found that patients who had been 'physically violent to others' were 39% more likely to dropout than those who had not.…”
Section: Case-mix Variablessupporting
confidence: 86%
“…A number of other factors may also explain differences between the two groups. Previous studies have found lower socio-economic status (SES) (Braet, Jeanin, Mels, Moens, & Van Winckel, 2010;Chisholm, Crowther, & Ben-Porath, 1997) and unemployment (Saxon, Ricketts, & Heywood, 2010) to be significant predictors of dropout.…”
Section: The Client Profilementioning
confidence: 99%
“…In fact, all of the studies reporting a significant relationship between the participant's age and treatment program completion found older offenders to be more successful than younger offenders (Edlund et al, 2009;Hickert et al, 2009;Mateyoke-Scrivner et al, 2004;Miller & Shutt, 2001;Olfson et al, 2009;Rempel & Destefano, 2002;Reneses et al, 2009;Rossi et al, 2002;Saum et al, 2001;Saxon et al, 2010). Rempel and Destefano (2002) theorized that younger substance abusing clients might be at a higher risk for dropout due to pressures from deviant peer groups.…”
Section: Client Characteristics Predictive Of Treatment Outcomementioning
confidence: 99%
“…Specifically, individuals who had a greater number of housing transitions over the 12 months prior to service delivery were more likely to fail to complete programming. Other studies reviewed did not examine the relationship between housing and program completion (Brown, 2010;Butzin et al, 2002;Edlund et al, 2009;Evans et al, 2009;Hartley & Phillips, 2001;Hickert et al, 2009;Miller & Shutt, 2001;Redlich et al, 2010;Rempel & Destefano, 2002;Reneses et al, 2009;Roll et al, 2005;Saum et al, 2001;Saxon et al, 2010;Sechrest & Shicor, 2001).…”
Section: Client Characteristics Predictive Of Treatment Outcomementioning
confidence: 99%